A pilot study of the effectiveness of the Maths For Life programme for children with Down syndrome - Gilligan-Lee, Katie A.; McGuigan, Karen; Snellgrove, Holly (Frontiers in Education, 2025)
Abstract Background: Beyond educational achievement, mathematics is essential for everyday living, e.g., telling the time, paying with money, using timetables. However, many children from neurodiverse populations fail to acquire basic mathematics skills in school. Aims: The aim of this study was to investigate if and how the Maths For Life programme, a new mathematical curriculum designed to help struggling learners, influences mathematics performance in children with Down syndrome. Methods and Procedure: Participants included 32 individuals with Down syndrome aged 5-to-24 years (Mage = 12.92 years, SD = 5.8). The study had a pre-post intervention design. The intervention group (n=15) completed the Maths For Life programme (administered by parent/guardian) in addition to their normal school classroom activities and the business-as-usual control group (n=17) completed their school mathematics classes only. Both groups completed a mathematics assessment pre/post the 4-month intervention period. Results: Following the programme, the intervention group had higher accuracy and independence scores compared to the business-as-usual control group. Conclusions and implications: The Maths For Life programme can help individuals with Down syndrome to improve their mathematical ability and independence, evidence that supports further testing this programme in schools. Improving children’s accurate and independent application of mathematics is vital for everyday living.